Peran Pemimpin dalam Meningkatan Kualitas Sumber Daya Manusia pada Lembaga Dakwah - Nia Darmawati; Cecep Castrawijaya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The role of leaders in da'wah institutions is very strategic in improving the quality of human resources (HR) who are the driving force of da'wah activities. Leaders function not only as directors of the organization's vision and mission, but also as facilitators of competency development, motivators, and role models in the implementation of da'wah values. This study aims to analyze how leadership styles, HR development strategies, and coaching approaches contribute to increasing the capacity of members in da'wah institutions. The research method used is descriptive qualitative with interview techniques and documentation studies. The results showed that adaptive, communicative, and value-based leaders were able to encourage significant individual and collective capacity building. Effective strategies include regular training, mentoring, empowering individual potential, and creating a supportive organizational culture. Thus, the success of a da'wah institution in achieving its goals is highly dependent on the effectiveness of the leader's role in fostering and improving the quality of human resources.